Silence Among First-Line Managers in Eldercare and Their Continuous Improvement Work During Covid-19 - Lotta Dellve Prof, PhD; Mimmi Kheddache Jendeby MSc (SAGE Publishing, 2022)
Eldercare sector faced severe needs, and unexplained difficulties, to manage daily work and the continuous improvement of routines at operative levels during Covid-19. First-line managers in eldercare have a key role to facilitate learnings but may be hindered in public, hierarchical organizations. This is the first study on the conditions and importance of silence for managerial work in terms of daily operations and continuous improvement work. To identify first-line managers' silence in eldercare, its contextual and supportive conditions, its reasons and its implications for managerial work with regard to daily operations and continuous improvement work. Mixed-method study based on a questionnaire to first-line managers (n = 189) in Swedish public eldercare in 33 randomly selected municipal organizations and one city. The instruments Communication of Critical Issues at Work, Managers Stress Inventory and Managerial Work and an open question were analyzed using: (1) qualitative coding to explore organizational conditions, (2) descriptive statistics, and (3) stepwise regressions to identify associations. The most common forms of silence were quiescent (based on fear of the consequences of speaking up) and acquiescent (based on resignation and demotivation). Organizational conditions shaping managerial silence were due to strict governance and control in a hierarchical organization, lack of support and participation in decision-making and the experience of not being valued. Managers' silence had a negative impact on managerial work and especially work on continuous improvements. The pandemic also offered space for values of occupational professionalism and learning at operational levels. Organizational conditions of support through superiors and management teams decreased silence. Manager silence is detrimental for continuous improvement work and may arise in organizations with dominant values of organizational professionalism. Supportive conditions based on trust and space for occupational professionalism may be important and should be improved to decrease managerial silence and better support continuous improvements.